2017
DOI: 10.20952/revtee.v10i22.6433
|View full text |Cite
|
Sign up to set email alerts
|

Schooling and subversions of gender

Abstract: The aim of this essay is to discuss bodies and discourses that question and confront gender norms and all possibilities of control of bodies in formative institutions. In order to do so, we analyzed three fi eld research scenes, performed in diff erent times and spaces. We show that they take place in the formative practices and spaces, there are several areas of subversion to norms and we face the control of bodies, as well as to show that these are dispute places, that in our research we do not generally pri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
3

Year Published

2019
2019
2021
2021

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 2 publications
0
2
0
3
Order By: Relevance
“…As discussões sobre gênero no espaço da academia são fundamentais para incentivar a renovação conceitual sobre a inclusão sexual e de gênero nas várias dimensões organizacionais das instituições (DIAS et al, 2017;MEDEIROS;SANTOS, 2020;PINTO et al, 2017;RIOS;. É por isso necessário colocar uma lente dissidente, não normativa, enquanto ato político sobre das questões de gênero, em conformidade com as influências dos estudos pós-identitários (DIAS; BRAZÃO, 2021).…”
Section: Considerações Iniciaisunclassified
“…As discussões sobre gênero no espaço da academia são fundamentais para incentivar a renovação conceitual sobre a inclusão sexual e de gênero nas várias dimensões organizacionais das instituições (DIAS et al, 2017;MEDEIROS;SANTOS, 2020;PINTO et al, 2017;RIOS;. É por isso necessário colocar uma lente dissidente, não normativa, enquanto ato político sobre das questões de gênero, em conformidade com as influências dos estudos pós-identitários (DIAS; BRAZÃO, 2021).…”
Section: Considerações Iniciaisunclassified
“…However, even with the implementation of the National Curriculum Parameters -PCN and the significant transformations that are happening in Brazilian society and educational field, it is observed that curricula have given little importance to the issues gender and sexual diversity, reproducing perverse logics of oppression against LGBTQ identities (DIAS et al, 2017). According to Dias and Menezes (2017) being suspicious about the school curriculum presents itself as pedagogical innovation from the queer perspective (DIAS et al 2017;DIAS, 2014;ULJENS, 2016, FINO 2016RUDD, T.;GOODSON, 2016). PCN's for Elementary School (BRASIL, 1997) bring references on gender and sexuality themes, but still falls short of being able to address them properly.…”
Section: The School As a Standardization Spacementioning
confidence: 99%
“…Dentre as inúmeras funções atribuídas à educação, ensinar o respeitar as diferenças, buscando educar para um convívio harmonioso, é sem dúvida um dos maiores desafios. Construir uma educação que tenha por base a inclusão, seja qual for a diferença, é fazer com que a escola desconstrua rótulos, estereótipos e preconceitos que ao longo do tempo foram sendo naturalizadas, como sendo a única verdade (DIAS;MENEZES, 2017;DIAS et al, 2017).…”
Section: A Abordagem Metodológica (Auto)biográficaunclassified